2012
DOI: 10.1017/s1355771811000380
|View full text |Cite
|
Sign up to set email alerts
|

Sound, Listening and Place: The aesthetic dilemma

Abstract: A purely aesthetic approach may be problematic when artists wish to deal with the external world as part of their work. The work of R. Murray Schafer in formulating soundscape studies is described, as well as the author's extension of that work within a communicational framework. Soundscape composition is situated within a continuum of possibilities, each with its own practice of mapping or representing the world. Current technological possibilities as well as ethical issues involved in the production process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 13 publications
(12 reference statements)
0
57
0
1
Order By: Relevance
“…In response, we can say that various applied research techniques and artistic performances have revealed different perspectives regarding the dynamics of soundscape composition, such as Barry Truax's virtual soundscapes (Truax 2012). The potentials of these practices as a method of inquiry and as an artistic performance have already been highlighted in the literature (Paquette and McCartney 2012).…”
Section: The Convergence Of Soundscape Studies and Ethnographymentioning
confidence: 99%
“…In response, we can say that various applied research techniques and artistic performances have revealed different perspectives regarding the dynamics of soundscape composition, such as Barry Truax's virtual soundscapes (Truax 2012). The potentials of these practices as a method of inquiry and as an artistic performance have already been highlighted in the literature (Paquette and McCartney 2012).…”
Section: The Convergence Of Soundscape Studies and Ethnographymentioning
confidence: 99%
“…Realtime spectral transformations and cross synthesis (Dynamic filtering of one signal, using the spectral envelope of another signal) has been explored during the last 30 years or so together with convolution [1,25]. Creative uses of convolution as a timbral transformative device in composition has been explored by [3][4][5]26,27], and the more performative aspects of real-time convolution by [28][29][30]. Common to all of these has been that the impulse response of the convolution process was static, and that any updates or dynamic replacement of the impulse response required some variation of a crossfading scheme between parallel convolution processes.…”
Section: Convolution and Other Sound Transformations Live Usementioning
confidence: 99%
“…Convolution has been used for filtering, reverberation, spatialisation, and as a creative tool for cross-synthesis in a variety of contexts [1][2][3][4][5]. Common to most of them is that one of the inputs is a time-invariant impulse response (characterising a filter, an acoustic space or similar), allocated, and preprocessed prior to the convolution operation.…”
Section: Introductionmentioning
confidence: 99%
“…Such physical, organizational and personal factors form an important contextual layer that is not addressed in standard soundscape investigation practices and is rarely addressed directly in soundscape research [3,4]. Sonic elements have been previously acknowledged as potentially defining and unifying for a community through time [5,6]; however, the particular agency of acknowledged historic spaces-and the vital layers of additional experiential, cultural and administrative context these deliver-requires more direct attention as soundscape investigation continues to be standardized.…”
Section: Introductionmentioning
confidence: 99%